2006
DOI: 10.1016/j.ijmultiphaseflow.2006.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic lengths and maximum entropy estimation from probe signals in the ellipsoidal bubble regime

Abstract: The bubble size, surface and volume distributions in two and three phase flows are essential to determine energy and mass transfer processes. The traditional approaches commonly use a conditional probability density function of chord lengths to calculate the bubble size distribution, when the bubble size, shape and velocity are known. However, the approach used in this paper obtains the above distributions from statistical relations, requiring only the moments inferred from the measurements given by a sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
(33 reference statements)
0
21
0
Order By: Relevance
“…It has been shown that the backward transformation is an unstable problem for all the aforementioned methods. Recently, Santana et al (2006) reported a different method that avoids the use of the backward transformation. They found a semiparametric solution of the problem by applying the maximum entropy method and applied it successfully to gas-liquid systems assuming an elliptical bubble shape.…”
Section: P(y|d)p(d) Ddmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the backward transformation is an unstable problem for all the aforementioned methods. Recently, Santana et al (2006) reported a different method that avoids the use of the backward transformation. They found a semiparametric solution of the problem by applying the maximum entropy method and applied it successfully to gas-liquid systems assuming an elliptical bubble shape.…”
Section: P(y|d)p(d) Ddmentioning
confidence: 99%
“…Moreover the sample size needed to obtain a reliable distribution is smaller than in the other methods. Santana et al (2006) successfully applied this method to gas-liquid systems assuming an elliptical bubble shape.…”
Section: P(y|d)p(d) Ddmentioning
confidence: 99%
“…The bubble eccentricity was obtained as the eccentricity of the ellipse that has the same second moments as the bubble and the bubble orientation was defined as the angle (in degrees) between the horizontal axis and the major axis of such ellipse. The Probability Density Functions (PDF) were obtained as the distributions p(x) that maximize the Shannon's entropy ∫ − p(x) ln (p(x))dx, restricted to a series of constrains that the distribution p(x) has to satisfy, which are the raw moments of the distribution 〈x i 〉 [27,28]: max∫−pðxÞ ln ðpðxÞÞdx ð5Þ…”
Section: Resultsmentioning
confidence: 99%
“…The mathematical procedure followed to obtain p(x) was similar to the one described in detail in [27]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation